Acute toxicity comparison of magnetic resonance‐guided adaptive versus fiducial or computed tomography‐guided non‐adaptive prostate stereotactic body radiotherapy: A systematic review and meta‐analysis - Leeman, Jonathan E.; Shin, Kee‐Young; Chen, Yu‐Hui; Mak, Raymond H.; Nguyen, Paul L.; D’Amico, Anthony V.; Martin, Neil E. (Cancer, 2023)
Background Stereotactic body radiotherapy (SBRT) is gaining wider adoption for prostate cancer management but there remain significant toxicity risks when delivering prostate SBRT with standard techniques. Magnetic resonance‐guided daily adaptive SBRT (MRg‐A‐SBRT) offers technological advantages in precision of radiation dose delivery, but the toxicity profile associated with MRg‐A‐SBRT compared to more standardly used fiducial or computed tomography‐guided non‐adaptive prostate SBRT (CT‐SBRT) remains unknown. Methods A meta‐analysis to compare acute toxicity rates associated with MRg‐A‐SBRT and CT‐SBRT for prostate cancer was performed in compliance with PRISMA guidelines. MEDLINE (PubMed) and Google Scholar were searched for prospective studies of prostate SBRT that were published between January 1, 2018 and August 31, 2022. Random effects and fixed effects models were used to estimate pooled toxicity rates, and meta‐regression was performed to compare toxicity between MRg‐A‐SBRT and CT‐SBRT study groups. Results Twenty‐nine prospective studies were identified that met the inclusion criteria and included a total of 2547 patients. The pooled estimates for acute grade 2 or higher (G2+) genitourinary (GU) and gastrointestinal (GI) toxicity for MRg‐A‐SBRT were 16% (95% confidence interval [CI], 10%–24%) and 4% (95% CI, 2%–7%) and for CT‐SBRT they were 28% (95% CI, 23%‐33%) and 9% (95% CI, 6%‐12%), respectively. On meta‐regression, the odds ratios for acute G2+ GU and GI toxicities comparing MRg‐A‐SBRT and CT‐SBRT were 0.56 (95% CI, 0.33–0.97, p = .04) and 0.40 (95% CI, 0.17–0.96, p = .04), respectively. Conclusion MRg‐A‐SBRT is associated with a significantly reduced risk of acute G2+ GU or GI toxicity compared to CT‐SBRT. Longer follow‐up will be needed to evaluate late toxicity and disease control outcomes. Plain language summary Magnetic resonance imaging‐guided daily adaptive prostate stereotactic radiation (MRg‐A‐SBRT) is a treatment that may allow for delivery of prostate radiation more precisely than other radiotherapy techniques, but it is unknown whether this reduces side effects compared to standardly used computed tomography‐guided SBRT (CT‐SBRT). In this systematic review and meta‐analysis combining data from 29 clinical trials including 2547 patients, it was found that the risk of short‐term urinary side effects was reduced by 44% and the risk of short‐term bowel side effects was reduced by 60% with MRg‐A‐SBRT compared to CT‐SBRT. This meta‐analysis of 29 prostate stereotactic body radiotherapy (SBRT) studies including 2547 patients found a reduction in the risk of acute urinary and gastrointestinal side effects with magnetic resonance‐guided adaptive SBRT compared to standard computed tomography‐guided SBRT.